The secular religion of Franklin Merrell-Wolff - Vliegenthart, Dave. (Leiden ; Boston)
viii, 378 sayfa
Keywords: “In The Secular Religion of Franklin Merrell-Wolff: An Intellectual History of Anti-intellectualism in Modern America, Dave Vliegenthart offers an account of the life and teachings of the modern American mystic Franklin Merrell-Wolff (1887-1985), who combined secular and religious sources from eastern and western traditions in order to elaborate and legitimate his metaphysical claim to the realization of a transcendental reality beyond reason. Using Merrell-Wolff as a typical example of a modern western guru, Vliegenthart investigates the larger sociological and historical context of the ongoing grand narrative that asserts a widespread anti-intellectualism in modern American culture, exploring developments in religious, philosophical, and psychological discourses in North America from 1800 until the present.“ --